1992
DOI: 10.1104/pp.100.1.518
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Photoevolution Indicates an Increase in the Antenna Size of Photosystem I in Chlamydobotrys stellata during Transition from Autotrophic to Photoheterotrophic Nutrition

Abstract: The changes in the light-harvesting antenna size of photosystem I were investigated in the green alga Chiamydobotrys stellata during transition from autotrophic to photoheterotrophic nutrition by measuring the light-saturation behavior of hydrogen evolution following single turnover flashes. It was found that during autotrophic-to-photoheterotrophic transition the antenna size of photosystem I increased from 180 to 250 chlorophyll. The chlorophyll (a + b)/P700 ratio decreased from 800 to 550. The electron tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It is clear that the biomass productivity found in this study ranked among the top ones in terms of total suspended solid concentration. There are reported evidences indicating that some heterotrophic algae utilize organic carbons more efficiently under light condition than in dark (McKinley and Wetzel, 1979;Boichenko et al, 1992). Furthermore, it was suggested that the growth rate for algae grown in mixotrophic way was almost the sum of autotrophic and heterotrophic growth (Lee, 2007).…”
Section: Comparison Of Biomass Concentration Total Lipid and Fatty Amentioning
confidence: 98%
“…It is clear that the biomass productivity found in this study ranked among the top ones in terms of total suspended solid concentration. There are reported evidences indicating that some heterotrophic algae utilize organic carbons more efficiently under light condition than in dark (McKinley and Wetzel, 1979;Boichenko et al, 1992). Furthermore, it was suggested that the growth rate for algae grown in mixotrophic way was almost the sum of autotrophic and heterotrophic growth (Lee, 2007).…”
Section: Comparison Of Biomass Concentration Total Lipid and Fatty Amentioning
confidence: 98%
“…In Chlamydomonas stellata, the antenna size of PS I might increase during transition from autotrophic nutrition to hydrogen evolution [21]. Therefore, a number of oxidized substrates, also known to be reducible by PS I, were applied seeking their probable competition with protons on photosynthetic electrons in the cyanobacterium O. chalybea.…”
Section: Resultsmentioning
confidence: 99%
“…The PSI content of cells was determined by the redox difference spectrum according to the method of Boichenko et al, using a differential excitation coefficient, ε = 64 mM −1 cm −1 at 700 nm . The PSII content was calculated as one half molar of the Cyt b 559 content of the cell, determined by the redox difference spectrum as previously described .…”
Section: Methodsmentioning
confidence: 99%